Investigation of the thermal behaviour of different biomasses and properties of their low- and high-temperature ashes. (1st October 2021) - Reinmöller, Markus; Sieradzka, Małgorzata; Laabs, Marcel; Schreiner, Marcus; Mlonka-Mędrala, Agata; Kopia, Agnieszka; Meyer, Bernd; Magdziarz, Aneta
Highlights: Two types of biomass are studied regarding their thermal behavior and ash properties. The chemical composition of their ashes is analyzed using XRF and SEM-EDX. Low- and high-temperatures ashes are investigated with respect to real processes. Mineral phase transformation in the ashes is studied at two ashing temperatures. The resulting ash fusion behavior is detected and modeled by FactSage™. Abstract: Biomasses are a promising way to reduce the CO2 emissions in many industrial processes for the generation of energy and chemical base materials. To enable them to be used in related thermochemical conversion processes, their thermal behaviour and ash properties, which are the main limiting factors, must be investigated. In the present study, four feedstocks from two types of biomass are studied. The thermal behaviour is determined by thermal gravimetry (TG), differential thermal gravimetry (DTG), and differential scanning calorimetry (DSC) analysis. Comparable behaviour with only minor deviations is achieved for all biomass samples, which is largely independent of the exact properties of the feedstocks. The key goal of this work was to compare the properties of ashes obtained under 550 °C (standard procedure) and 200 °C (using plasma). Chemical analysis (applying X-ray fluorescence method) indicates the differences in the ash composition even in the particular types of biomass. Scanning electron microscopy (SEM-EDX) reveals that the composition is heterogeneously distributed over the different ash particles. Based on the different ashing temperatures, the transformation of the mineral phases in real conversion processes determined by X-ray diffraction (XRD) is simulated. Despite the heterogeneities in the ash particles' chemical composition and distribution within each particular type of biomass, they demonstrate highly similar ash fusion temperatures. The thermochemical calculations using the FactSage™ software package have well reflected the ash fusion temperatures and the ash fusion interval.